Fortalecimiento del control inhibitorio y flexibilidad cognitiva a través de la ludificación (2024)
Studies and research have shown that play contributes to meaningful learning and to different aspects of life, from childhood to adulthood. The present study evaluated the strengthening of inhibitory control and cognitive flexibility through gamification. The sample chosen was of 50 students from the Villanueva IED, where 2 groups were organized, one control and the other experimental. Two psychological tests were applied to both groups: the Stroop colors and words test and the ENFEN, Rings, in order to evaluate their cognitive flexibility and inhibitory control. An intervention plan was applied to the experimental group with the main objective of gamification to strengthen inhibitory control and cognitive flexibility. Subsequently, a comparison was made with both groups, indicating that in terms of inhibitory control there was a statistically significant difference with respect to pretest with an estimate of the median effect size (d: 0.56), and in terms of cognitive flexibility there was a significant difference with respect to pretest, showing that there was a large effect size (d: -1.05). In conclusion, gamification activities become tools to strengthen inhibitory control and cognitive flexibility in school children between 6 and 7 years old